1995
DOI: 10.1073/pnas.92.16.7575
|View full text |Cite
|
Sign up to set email alerts
|

Functional and developmental studies of the peripheral arterial chemoreceptors in rat: effects of nicotine and possible relation to sudden infant death syndrome.

Abstract: The drive on respiration mediated by the peripheral arterial chemoreceptors was assessed by the hyperoxic test in 3-day-old rat pups. They accounted for 22.5 ± 8.8% during control conditions, but only for 6.9 + 10.0% after nicotine exposure, an effect counteracted by blockade of peripheral dopamine type 2 receptors (DA2Rs). Furthermore, nicotine reduced dopamine (DA) content and increased the expression of tyrosine hydroxylase (TH) in the carotid bodies, further suggesting that DA mediates the acute effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 49 publications
4
54
0
1
Order By: Relevance
“…In addition, we show that an ingredient of cigarette smoke, i.e., nicotine, which has previously been reported to attenuate the protective CB arterial chemoreflex response when administered chronically in mammals (Holgert et al, 1995), mimics the effect of chronic hypoxia in causing elevation of basal DA release in CB cultures. In general, the regulation of extracellular DA is likely to be important for CB function since the prevailing evidence suggests that released DA, acting via pre-and postsynaptic D 2 receptors, inhibits the CB hypoxic ventilatory response (see Gonzalez et al, 1994;Holgert et al, 1995) and appears to be involved in the resetting of CB chemosensitivity in the perinatal period (Hertzberg et al, 1990). In a recent study (Jackson and Nurse, 1997), we found that basal DA release was substantially elevated in rat CB cultures after chronic hypoxia in vitro.…”
Section: Down-regulation Of Da Transporters In Cultures Exposed Chronmentioning
confidence: 86%
See 3 more Smart Citations
“…In addition, we show that an ingredient of cigarette smoke, i.e., nicotine, which has previously been reported to attenuate the protective CB arterial chemoreflex response when administered chronically in mammals (Holgert et al, 1995), mimics the effect of chronic hypoxia in causing elevation of basal DA release in CB cultures. In general, the regulation of extracellular DA is likely to be important for CB function since the prevailing evidence suggests that released DA, acting via pre-and postsynaptic D 2 receptors, inhibits the CB hypoxic ventilatory response (see Gonzalez et al, 1994;Holgert et al, 1995) and appears to be involved in the resetting of CB chemosensitivity in the perinatal period (Hertzberg et al, 1990). In a recent study (Jackson and Nurse, 1997), we found that basal DA release was substantially elevated in rat CB cultures after chronic hypoxia in vitro.…”
Section: Down-regulation Of Da Transporters In Cultures Exposed Chronmentioning
confidence: 86%
“…Since nicotine can be readily transferred to the infant via the placenta prenatally and in breast milk postnatally (for refs. see Holgert et al, 1995), the possibility of continuous nicotine exposure in the perinatalperiod is quite high for the offspring of smoking mothers. Previous studies suggest that chronic nicotine administration to perinatal rats induces release and synthesis of CB DA, which acts on local D 2 recep-tors to produce inhibition of the hypoxic drive (Holgert et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dopamine is an inhibitory neuromodulator in this system, and a decrease in dopamine levels is generally noted after birth to facilitate oxygen sensitivity and normal breathing (Hertzberg et al, 1990). However, 12-24 hr after postnatal nicotine exposure in rat pups, carotid body dopamine and mRNA expression of the catecholamine synthesizing enzyme, tyrosine hydroxylase, increase, resulting in an inhibition of chemoreceptor sensitivity (Holgert et al, 1995). An increase in dopamine levels has also been seen in rat pups after prenatal (6 mg/kg/day) nicotine administration and early in the postnatal period through lactational exposure (Gauda et al, 2001).…”
Section: Mechanismsmentioning
confidence: 99%